(untitled) (Global Journal of Human-Social Science, 2014)
Thi s study examined crimes situations and reaction of criminal justice system in Oromia, Ethiopia. It attempted to analyze incidence and types of crime, determine crime and criminal rate, appraise the efficiency and measures taken by criminal justice system, and provide possible explanations on crime situations using a selected theoretical framework. Socio- cultural theoretical frame work is used in explaining factors of crime. The study was conducted in Oromia National Regional State for a